Development of Material Use Scale in Mathematics Teaching - (:unkn) unknown (ICLEL CONFERENCES, 2017)
The academic achievement of the students is influenced by four basic factors, themselves, their social environment, physical conditions and education. The education factor consists of four basic subfactors: teacher, method, environment and material. As one of the basic principles which is valid for all educational factors, when more senses of the student is addressed, learning becomes easier. The training materials that contribute to the inclusion of multiple senses in the course of learning increase the success in learning. One of the reasons for the low student achievement in mathematics is the abstract formation and the lack of connection ability of the student between the abstract and the concrete. In this context, materials in mathematics education gain more importance. Much more attention should be paid in mathematics lesson to the use of educational materials that serve to improve mathematical thinking in the pupils. It is highly likely that teachers attitudes and behaviors of using materials is effective in mathematics lesson, where student achievement is lowest in Turkey. The study was conducted with mathematics teachers (n=275) who were working in the spring semester of 2016-2017 in Edirne, Tekirdag, Kirklareli. The data collection tool was the Scale of Material Use in Mathematics Teaching prepared by the researchers. The scale consists of 41 items each with 4 grades. To determine sub-dimensions (8) as scale development statistics, the varimax rotated exploratory factor analysis has been used. Internal consistency has been determined by calculating item-total correlation coefficient and item-remainder correlation coefficient for each sub-dimension. Similarly, Discriminant Coefficients of the items has been determined by applying the t-test in the upper and towel . quarters. The Cronbach and Rulon coefficients have been calculated for the scale and its sub-dimensions to determine reliability. It has been established by statistical processing that the scale comprising 8 factors is valid, reliable and usable.
Keywords: mathematics teaching; educational material use; reliability